Legal Challenges in the Trading of Sharia-Compliant Stocks in Indonesia: A Juridical and Sharia Perspective - Sarah Syakira (Journal of Economicate Studies, 2025)
This article examines the legal challenges associated with the trading of Sharia-compliant stocks in Indonesia from both juridical and Sharia perspectives. The study highlights the complexities arising from the intersection of Islamic law principles and national capital market regulations. Using a qualitative descriptive approach, the research analyzes regulatory frameworks, fatwas issued by the National Sharia Council–Majelis Ulama Indonesia (DSN-MUI), and provisions from the Financial Services Authority (OJK). The findings reveal that despite the existence of a Sharia capital market framework, several legal ambiguities remain—particularly regarding compliance verification, investor protection, and dispute resolution mechanisms. The study emphasizes the need for harmonization between positive law and Sharia principles to strengthen legal certainty and investor confidence in Indonesia’s Islamic capital market. The paper contributes to the ongoing discourse on aligning financial innovation with Sharia compliance within the national regulatory structure.